2006
DOI: 10.1128/jvi.00688-06
|View full text |Cite
|
Sign up to set email alerts
|

All Three Variable Regions of the TRIM5α B30.2 Domain Can Contribute to the Specificity of Retrovirus Restriction

Abstract: Recent studies have revealed the contribution of TRIM5␣ to retrovirus restriction in cells from a variety of primate species. TRIM5␣ consists of a tripartite motif (the RBCC domain) followed by a B30.2 domain. The B30.2 domain is thought to be involved in determination of restriction specificity and contains three variable regions. To investigate the relationship between the phylogeny of primate TRIM5␣ and retrovirus restriction specificity, a series of chimeric TRIM5␣ consisting of the human RBCC domain follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
142
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(156 citation statements)
references
References 66 publications
12
142
1
1
Order By: Relevance
“…In contrast, V1-V3 of PRY/SPRY rh do not fall into either group, and V1 is significantly longer. These findings reinforce the notion that the variable regions of TRIM5α PRY/SPRY are mostly flexible and have evolved for antiviral activity (29)(30)(31).…”
Section: Resultssupporting
confidence: 85%
“…In contrast, V1-V3 of PRY/SPRY rh do not fall into either group, and V1 is significantly longer. These findings reinforce the notion that the variable regions of TRIM5α PRY/SPRY are mostly flexible and have evolved for antiviral activity (29)(30)(31).…”
Section: Resultssupporting
confidence: 85%
“…TRIM5α restriction is species-and virus-specific, and the specificity of restriction is largely determined by interactions between the C-terminal SPRY/B30.2 domain and the intact retroviral capsid. Although structural details are still lacking, mutational studies and sequence analyses of different SPRY alleles have provided insights into the determinants of capsid recognition (e.g., see [138][139][140][141]). In TRIM-Cyp, the SPRY domain of TRIM5α is replaced by cyclophilin A (CypA), a well-known peptidyl prolyl isomerase.…”
Section: Capsid Restrictionmentioning
confidence: 99%
“…Construction of chimeric genes in which these three variable regions are swapped between TRIM5a orthologues showed that all three of them can potentially contribute to restriction specificity. 32 Particular attention has been given to the v1 region, which is rich in positively (that is, non-randomly) selected aminoacids. 33,34 Versions of human TRIM5a in which short stretches of the v1 region were replaced by those of the macaque orthologue showed restriction activity against HIV-1.…”
Section: Introductionmentioning
confidence: 99%